Molecular characterization of a conserved 20-kilodalton membrane-associated lipoprotein antigen of Helicobacter pylori. - Kostrzynska, M (1994)
Antisera raised in rabbits to whole cells of Helicobacter pylori recognized as a major antigen a protein with an apparent molecular weight of 20,000. The antigen was purified by differential solubilization with N-octyl-beta-D-glucopyranoside, urea, and sodium dodecyl sulfate followed by molecular sieving. The mass of the protein, Lpp20, was 18,283 Da as determined by mass spectrometry. The lpp20 gene encoding this protein was cloned in Escherichia coli by using the vector lambda EMBL3, and plasmid subclones expressed the full-length protein from the native H. pylori promoter. lpp20 was mapped to the same 358-kb NruI fragment as flaB. DNA sequence analysis showed that the gene was 525 bp long and encoded a 175-amino-acid protein with a molecular weight of 19,094 containing a 21-residue typical lipoprotein signal peptide and consensus prolipoprotein processing site. The mass of the deduced 154-residue mature protein was 16,865 Da. Growth of E. coli cells expressing the cloned H. pylori lpp20 gene in the presence of [3H]palmitic acid resulted in radiolabelled Lpp20 while treatment of the E. coli cells with globomycin caused accumulation of unprocessed Lpp20, consistent with Lpp20 being a lipoprotein. Lpp20 cofractionated with the cytoplasmic membrane fraction, although a proportion of the protein was also found in the outer membrane. A mutant generated by mutant-allele exchange displayed normal viability, showing that Lpp20 belonged to the nonessential class of lipoproteins.